2003
DOI: 10.1097/01.wcb.0000050063.57184.3c
|View full text |Cite
|
Sign up to set email alerts
|

Absolute Cerebral Blood Volume and Blood Flow Measurements Based on Synchrotron Radiation Quantitative Computed Tomography

Abstract: Summary: Synchrotron radiation computed tomography opens new fields by using monochromatic x-ray beams. This technique allows one to measure in vivo absolute contrast-agent concentrations with high accuracy and precision, and absolute cerebral blood volume or flow can be derived from these measurements using tracer kinetic methods. The authors injected an intravenous bolus of an iodinated contrast agent in healthy rats, and acquired computed tomography images to follow the temporal evolution of the contrast ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 63 publications
4
32
2
Order By: Relevance
“…This SNR allows consistent regional CBVf measurements for different structures of the rat brain, as shown in Figure 4A (n = 6). For instance, the blood volume fraction of 2.92%70.68% in the striatum, which is a mixture of gray and white matter as it is traversed by fibers from the cortex, is lower than the blood volume fraction of pure gray matter such as the cortex (3.13%70.91%) and higher than the one of white matter (2.00%70.50%) in accordance with (Adam et al, 2003). The ratios of regional CBVf between cortex and striatum CBVf cortex /CBVf striatum of 1.1170.18 as well as between gray matter and white matter CBVf GM /CBVf WM of 1.5970.51 obtained in healthy normocapnic rats (n = 6) are also in the range reported in the literature ( Table 2).…”
Section: Normocapnic Cerebral Blood Volume Fraction Measurementsmentioning
confidence: 95%
“…This SNR allows consistent regional CBVf measurements for different structures of the rat brain, as shown in Figure 4A (n = 6). For instance, the blood volume fraction of 2.92%70.68% in the striatum, which is a mixture of gray and white matter as it is traversed by fibers from the cortex, is lower than the blood volume fraction of pure gray matter such as the cortex (3.13%70.91%) and higher than the one of white matter (2.00%70.50%) in accordance with (Adam et al, 2003). The ratios of regional CBVf between cortex and striatum CBVf cortex /CBVf striatum of 1.1170.18 as well as between gray matter and white matter CBVf GM /CBVf WM of 1.5970.51 obtained in healthy normocapnic rats (n = 6) are also in the range reported in the literature ( Table 2).…”
Section: Normocapnic Cerebral Blood Volume Fraction Measurementsmentioning
confidence: 95%
“…A study using synchrotron-based quantitative CT found CBV in the parietal cortex and in the caudate putamen to be 2.1± 0.38 mL/100 g and 1.92±0.32 mL/100 g respectively (Adam et al, 2003). Our relative CBV values (not specific to arteries, but including both arterial and venous CBV in the region) for cortical and subcortical gray matter were 0.89±0.08 and 0.61±0.09, and were not significantly 7.…”
Section: Steady State Hemodynamic Parameters Vary Across the Brainmentioning
confidence: 98%
“…1 Nevertheless, there is also a great interest in providing consistent perfusion estimation which, with different methods, differs by a fair amount. [2][3][4] As stated by Kudo et al,4 little is known about the relationship between CBF measured with different methods. The CBF estimations with computed tomography perfusion (CT perfusion), positron emission tomography (PET), or single-photon emission computed tomography are thus very difficult to compare, even if correcting for large vessel over-contribution in CT perfusion leads to more consistent results.…”
Section: Introductionmentioning
confidence: 99%